Geosynthetics and their applications - Shukla, Sanjay Kumar (Thomas Telford, 2002)
Geosynthetics are being used extensively throughout the world as they offer the most efficient and cost-effective solutions of a myriad of civil engineering problems. If properly protected, geosynthetics have the potential of functioning for hundreds of years. Rational design methods are now available, placing the use of geosynthetics on a firm base.